Albuminuria and reduced glomerular filtration rate for predicting the renal outcomes in type 2 diabetic patients. (August 2015) - Tanaka, Nobue; Babazono, Tetsuya; Takagi, Michino; Yoshida, Naoshi; Toya, Kiwako; Nyumura, Izumi; Hanai, Ko; Uchigata, Yasuko
Abstract: Aim: The first clinical manifestation of diabetic kidney disease is usually the development of microalbuminuria. However, recent studies have focused on diabetic patients with reduced glomerular filtration rate (GFR) without albuminuria. To evaluate the association of albuminuria and GFR with renal outcomes, we performed an observational study. Methods: A total of 3231 type 2 diabetic patients were included in this study between 2003 and 2005. There were 1249 women and the mean age was 59 ± 12 years. The renal endpoints were defined as the initiation of renal replacement therapy (RRT) or 50% reduction from the baseline of estimated GFR (eGFR). Results: At baseline, 669 (20.7%) patients had eGFR <60 mL/min per 1.73 m 2 and 1134 (35.1%) had albuminuria. During the mean follow‐up period of 5.9 ± 1.6 years, 107 patients initiated RRT. A 50% reduction of eGFR from the baseline value was found in 279 patients. None of the normoalbuminuric subjects with or without reduced eGFR required RRT during the observational period ( P < 0.01). Compared to normoalbuminuria patients with eGFR ≥60 mL/min per 1.73 m 2 at baseline, the group of normoalbuminuria patients with reduced eGFR had a 2.5‐fold risk of developing the renal endpoints, (95% confidence interval (CI): 1.0–6.3, P = 0.053). Patients with microalbuminuria with eGFR ≥60 mL/min per 1.73 m 2 at baseline had a 5.0‐fold risk of developing the evaluated renal endpoints (95% CI: 2.8–8.8, P < 0.001). Conclusion: Albuminuria was a significant predictor for the evaluated renal endpoints, but the impact of eGFR is likely to be less than that of albuminuria. Summary at a Glance: This paper examines renal outcomes (as defined by initiation of renal replacement therapy or 50% reduction in eGFR) in over 3000 Japanese patients followed‐up for nearly 6 years, demonstrating low progression to ESKD in the absence of albuminuria, but an elevated risk of mortality. This is an interesting study highlighting the prognostic importance of albuminuria in a Japanese population.